The Drought Hazard: Risk Perceptions and Educational Actions that Promote Resilience in the Cuban Population - Elizabet Godefoy Núñez; Sahilí Cristiá Lara (Agrisost, 2021)
Context: The study of subjectivity in face of natural dangers is being conducted in Cuba as part of the Studies of Hazard, Vulnerability, and Risk by the Environmental Agency of CITMA in Cuban provinces. Droughts require control plans that reduce the negative effects of droughts and the repercussions on the population exposed.